Pengaruh Maqôsid Syari’ah Di Dalam Tafsir dan Hadis - Zuhurul Fuqohak, Mukhamad Agus (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2020)
This research is intended to find out the meaning of the study maqôsidi in the interpretation, to look for the historical roots of the use of maqôsid as an independent branch of knowledge, who are the scholars who are keen to concentrate on the maqôsid theory then what are the examples of maqôsid usage in the world of the Qur'anic interpretation. This study uses qualitative without mentioning numbers, the primary source of this literature study from several master books such as the Asy-Syâthibi book which is famous as the father of maqôsid. Then the result of the findings is that the intention of the maqôsid in the world of interpretation is the review of the Qur'an seeking wisdom, reasons and lessons to get a kind of wordl view from it. Then the history begins with Umar bin Khattab, Imam Haromain, Ghazali, Asy-Syâthibi, Ibnu ‘Âsyûr to ar-Raisûni. Which is an example of the use of maqôsid in interpretation is the interpretation of QS. Al-Mâidah: 51, QS. Al-Mâidah: 6 QS. Al-Baqarah: 187.